Chromatin Dynamics in Cellular Function - Laurent, Brehon C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
This volume includes timely reviews of several aspects of chromatin biology written by scientists at the forefront of this rapidly moving field. Topics covered include the structure and function of protein modules within chromatin-remodeling proteins, newly characterized histone modifications (methylation, ubiquitylation) and their functional consequences, transcription and histone dynamics, roles of chromatin remodeling factors in DNA replication and repair, and current models of nucleosome-remodeling mechanisms.
Structure and Function of Protein Modules in Chromatin Biology -- The Generation and Recognition of Histone Methylation -- Histone Ubiquitylation and the Regulation of Transcription -- Histone Dynamics During Transcription: Exchange of H2A/H2B Dimers and H3/H4 Tetramers During pol II Elongation -- The Roles of Chromatin Remodelling Factors in Replication -- Chromatin Modifications in DNA Repair -- Mechanisms for Nucleosome Movement by ATP-dependent Chromatin Remodeling Complexes.
Keywords: Life sciences; Biochemistry; Cell biology; Life Sciences; Cell Biology; Biochemistry, general; Electronic books